A qualitative study on fathers’ participation in substance use treatment - Aktürk, İlker and Yaman, Ömer Miraç (Journal of Dependence, 2022)
Objective: There is not enough information about the functions of fathers in substance use treatment. The primary aim of this study is to try to determine the father’s position in addiction treatment. Method: In this context, in-depth interviews were conducted with 20 substance users and 20 fathers of substance users. The data obtained from the interviews were analyzed using the descriptive analysis method, which is one of the qualitative data analysis methods. Results: Five different themes have been identified: Deficient Treatment Engagement in Fathers, Success Stories and Desire for Recovery as a Motivation Sources for Fathers in Engagement in Treatment, Function of Father’s Engagement in the Treatment Process, Create the Right Information and Relationship Network in Treatment, Differences between Mother and Father to Engagement in the Treatment Process. Conclusion: Fathers did not provide adequate participation in substance use treatment, and they were on the side that provided more financial support. However, meeting recovered substance users or having hope for treatment affects fathers’ participation in treatment. Another prominent factor in the study is that fathers’ participation in treatment can have a positive effect on the treatment process and may have significant effects on termination. Considering that fathers can quickly become disappointed and stay out of treatment during the treatment process, fathers need to reach the right information and the right source. Finally, significant differences were identified between mothers and fathers in participation in the treatment process. While the father provides financial support, the mother provides moral support and stands by her child against the father.